2004
DOI: 10.1523/jneurosci.0701-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Population Response of A- and C-Fiber Nociceptors in Monkey Encodes High-Intensity Mechanical Stimuli

Abstract: The peripheral neural mechanism of pain to mechanical stimuli remains elusive. C-fiber nociceptors do not appear to play a major role in mechanical pain sensation, because the stimulus-response function of mechanically sensitive C-fiber nociceptors to punctate mechanical stimuli applied to the most sensitive region in the receptive field (the hot spot) reaches a plateau at force levels insufficient to produce pain in humans. However, studies at the hot spot give an incomplete understanding of the inputs of noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…It can be seen that the FI curve of the Aδ-Neuroid matched the experimental curve (Figure 2c), whereas the FI curve of the HTC-Neuroid increased monotonically (Figure 2f) instead of reaching a plateau as reported previously by Slugg et al (2000). However, in a subsequent study (Slugg et al, 2004), it was demonstrated that the average response of C-fiber nociceptors across the receptive field does not reach a plateau, but increases monotonically with mechanical stimulus intensity. This suggests that the Neuroid might be used to predict the "average" response of a specific subpopulation of nociceptive primary afferents as long as the variability of experimental data is taken into account.…”
Section: The Neuroid As the Main Building Block For The Modeling Of Psupporting
confidence: 81%
See 1 more Smart Citation
“…It can be seen that the FI curve of the Aδ-Neuroid matched the experimental curve (Figure 2c), whereas the FI curve of the HTC-Neuroid increased monotonically (Figure 2f) instead of reaching a plateau as reported previously by Slugg et al (2000). However, in a subsequent study (Slugg et al, 2004), it was demonstrated that the average response of C-fiber nociceptors across the receptive field does not reach a plateau, but increases monotonically with mechanical stimulus intensity. This suggests that the Neuroid might be used to predict the "average" response of a specific subpopulation of nociceptive primary afferents as long as the variability of experimental data is taken into account.…”
Section: The Neuroid As the Main Building Block For The Modeling Of Psupporting
confidence: 81%
“…Discrepancies may be attributed to differences in the experimental protocol used to quantify the response properties of primary afferent and dorsal horn neurons (current injection vs. peripheral stimuli; in vivo vs. in vitro). While Neuroids representing primary afferent neurons were configured according to the response of these cells to peripheral mechanical stimuli (Cain et al, 2001;Slugg et al, 2000Slugg et al, , 2004, Neuroids representing dorsal horn neurons were configured according to the response of these cells to current injections (Ruscheweyh and Sandkühler, 2002), since no recent studies seem to be available to extract relevant features of the dorsal horn neurons responses to peripheral mechanical stimuli (e.g. the frequencyintensity curve).…”
Section: An Overview Of the Input-output Relationship At The Sdhmentioning
confidence: 99%
“…In primates, it has been shown that high-intensity mechanical punctate stimuli (e.g., von Frey probes) are capable of activating A␦-and C-fiber nociceptors (Slugg et al 2004). However, in healthy humans, von Frey stimulation usually does not cause pain.…”
Section: Effect Of Hfs On the Responses To Mechanical Stimulimentioning
confidence: 99%
“…In fact, the flatness observed in C-fiber responses suggested that they could not encode high intensity mechanical stimuli. Subsequent studies show that the average response of C-fiber nociceptors across the receptive field does not reach a plateau, but increases monotonically with stimulus intensity (Slugg et al, 2004). This leads to the assumption that individual and collective responses of Aβ-fibres may also differ.…”
Section: Introductionmentioning
confidence: 99%